MANAJEMEN ASUHAN KEBIDANAN ANTENATAL PATOLOGI DENGAN HIPEREMESIS GRAVIDARUM TUNGKAT II (LITERATURE REVIEW) - Melinda; Sitti Saleha; Syatirah (Jurnal Midwifery, 2022)
Introduction Hyperemesis gravidarum is a health issue often found during gestational period signified by a severe and excessive nausea and vomiting. Once a mother experiences an excessive nause and vomitting, she will probably lose her weight. In addition, a mother will also suffer from acetone and skin dryness. Nausea and vomiting in pregnancy usually begins in the 9th to 10th weeks of gestational period. It would mostly become worse in 11th to 13th weeks. In general, the issues would end in the 12th to 14th weeks. The data shows that rarely do pregnancy’ssymptoms persist to be more the 20th to 22nd week. The proportion has been only around 1-10%. For the cases of hyperemesis gravidarum, they were found on 0.3-2% of pregnancies in which patients should be well treated in a hospital. Method The methodological approach used in this research was literature review. The major purpose was to conduct research on the issue related to hyperemesis gravidarum. The research was conducted based on the 7-stages of Varney and SOAP documentation procedures. Result Based on the research data analysis from various different references, it could be noticed that the treatments that could be given to patients with hyperemesis gravidarum were in the forms of providing adequate parenteral fluids as well as administering protein electrolytes with 5% of glucose dissolved into 2 to 3 liters of physiologist saline. In addition, other important potions such as potassium depending on the conditon of patients. Initial fluid administration could also be given in the forms of 2L RL solvent for approximately 3-5 hours. The fluid should further be replaced with 5% of dextrose dissolved in 0.45% of saline. The RL dextrose ratio of 2:1 could be implemented with 40 drops per minute to be given to patients. Conclusion The findings of this research were the results of the analysis on 70 references. It could be concluded that with appropriate treatments and medication, patients with the case of hyperemesis gravidarum could be cured. The major examination that could be taken to confirm the status of patients is by checking the vital signs such as blood pressure, pulse, temperature and respiration